THE INFLUENCE OF JOB SATISFACTION AND MOTIVATION ON EMPLOYEE PERFORMANCE CV. OSCAR FURNITURE SURABAYA - Fitri Ayuningtyas; Hesti Pandu Widodo; Achmad Daengs GS; Enny Istanti; Ruchan Sanusi (PT. Mawadaku Sukses Solusindo, 2023)
This study aimed to clarify wether the variable Job Satisfaction and Work Motivation significant influence on employees performance at CV.OSCAR FURNITURE Surabaya as well as to determine which variables are the dominant influence of the two fariable Job Satisfaction and Work Motivation on the performance of employees at CV. OSCAR FURNITURE Surabaya.The sample of using Census sampling method is directly choosing 30 persons of the employees. The data collection methods that used were interview the parties that involved with the issues being discussed directly and gave questionnaires ti the employees in accordance with the research conducted. The data were analyzed with using Quantitative Methods that using four formulas: Multiple Regression Analysis, T test, F test and the coefficient of determination (R2) test with the aid of SPSS 16.0 software for windows. The results showed that jointly Job satisfaction and work motivation significantly Influence the performance of employees at CV.OSCAR FURNITURE Surabaya. Variable Job Satisfaction and Work Motivation regression coefficientis positive indicates a unidirectional relationship, in other words, Job Satisfaction and Work Motivation will improve the performance of employees at CV.OSCAR FURNITURE Surabaya